Comparison of efficacy and adverse effects of Triptans and Gepants – Anti-migraine drugs - Tabasum, Pakeezah; Fatima, Wajiha; Adnan, FNU (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Migraine, the 2nd largest cause of Years Lived in disabilities (YLD) in 195 countries of world with a prevalence rate of 1040 Million. It is unilateral neurological disorder of head. 75% of patient of migraine are female who are in their reproductive stage. Most probably, the accepted cause behind pathophysiology of migraine is dilation of cephalic and intracranial arteries. By decades, the commonest used drugs for acute treatment of migraine are Triptans, 5-HT 1B and 5-HT1D receptor antagonist. Triptans for the treatment of migraine, cause relief from pain and other symptoms of migraine such as, nausea, vomiting, photophobia and photophobia within 2 hours. However, newly approved Drugs: Zavegepant and Rimegepant cause greater adverse effect than Triptans. Hence, rarely used for the treatment of migraine due its greater complications.